The Role of Emotional Intelligence and Organizational Culture in Improving Employee Performance: Empirical Evidence from Gajah Sakti Village - Prabowo, Aji; Nadeak, Putry H.; Silaen, Karina; Fiannisa, Muharani (Jurnal Ilmu Manajemen dan Ekonomika, 2025)
This research aims to determine the role of emotional intelligence and organizational culture in improving employee performance: empirical evidence from Gajah Sakti Village. Gajah Sakti Village faces several labor-related issues with low performance associated with discipline and initiative. These problems can be linked to low emotional intelligence and poor organizational culture. This study employs a quantitative approach using a survey method involving 80 respondents. The analysis using the Partial Least Square (PLS) method shows that emotional intelligence and organizational culture have a positive and significant impact on employee performance. This means that the higher the emotional intelligence, the better the organizational culture, and the better the employee performance. This study recommends that the village government hold workshops on emotional intelligence and improve the organizational culture to enhance employee performance.